Specialized box C/D snoRNPs act as antisense guides to target RNA base acetylation. - Sunny Sharma; Jun Yang; Rob van Nues; Peter Watzinger; Peter Kötter; Denis L J Lafontaine; Sander Granneman; Karl-Dieter Entian (PLoS Genetics)
Box C/D snoRNAs are known to guide site-specific ribose methylation of ribosomal RNA. Here, we demonstrate a novel and unexpected role for box C/D snoRNAs in guiding 18S rRNA acetylation in yeast. Our results demonstrate, for the first time, that the acetylation of two cytosine residues in 18S rRNA catalyzed by Kre33 is guided by two orphan box C/D snoRNAs-snR4 and snR45 -not known to be involved in methylation in yeast. We identified Kre33 binding sites on these snoRNAs as well as on the 18S rRNA, and demonstrate that both snR4 and snR45 establish extended bipartite complementarity around the cytosines targeted for acetylation, similar to pseudouridylation pocket formation by the H/ACA snoRNPs. We show that base pairing between these snoRNAs and 18S rRNA requires the putative helicase activity of Kre33, which is also needed to aid early pre-rRNA processing. Compared to yeast, the number of orphan box C/D snoRNAs in higher eukaryotes is much larger and we hypothesize that several of these may be involved in base-modifications.